CSA13 inhibits colitis-associated intestinal fibrosis via a formyl peptide receptor like-1 mediated HMG-CoA reductase pathway. Issue 1 (December 2017) - Xu, Chunlan; Ghali, Sally; Wang, Jiani; Shih, David; Ortiz, Christina; Mussatto, Caroline; Lee, Elaine; Tran, Diana; Jacobs, Jonathan; Lagishetty, Venu; Fleshner, Phillip; Robbins, Lori; et al.
Abstract Many Crohn's disease (CD) patients develop intestinal strictures, which are difficult to prevent and treat. Cationic steroid antimicrobial 13 (CSA13) shares cationic nature and antimicrobial function with antimicrobial peptide cathelicidin. As many functions of cathelicidin are mediated through formyl peptide receptor-like 1 (FPRL1), we hypothesize that CSA13 mediates anti-fibrogenic effects via FPRL1. Human intestinal biopsies were used in clinical data analysis. Chronic trinitrobenzene sulfonic acid (TNBS) colitis-associated intestinal fibrosis mouse model with the administration of CSA13 was used. Colonic FPRL1 mRNA expression was positively correlated with the histology scores of inflammatory bowel disease patients. In CD patients, colonic FPRL1 mRNA was positively correlated with intestinal stricture. CSA13 administration ameliorated intestinal fibrosis without influencing intestinal microbiota. Inhibition of FPRL1, but not suppression of intestinal microbiota, reversed these protective effects of CSA13. Metabolomic analysis indicated increased fecal mevalonate levels in the TNBS-treated mice, which were reduced by the CSA13 administration. CSA13 inhibited colonic HMG-CoA reductase activity in an FPRL1-dependent manner. Mevalonate reversed the anti-fibrogenic effect of CSA13. The increased colonic FPRL1 expression is associated with severe mucosal disease activity and intestinal stricture. CSA13 inhibits intestinal fibrosis via FPRL1-dependent modulation of HMG-CoA reductase pathway.